2021
DOI: 10.1039/d1dt01742j
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal synthesis of metal chalcogenide nanomaterials from metal–organic precursors and capping ligand effect on electrocatalytic performance: progress, challenges and future perspectives

Abstract: Renewable and sustainable functional nanomaterials, which can be employed in alternative green energy sources, are highly desirable. Transition metal chalcogenides are potential catalysts for processes resulting in energy generation and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 88 publications
0
24
0
Order By: Relevance
“…Overall, the relatively similar electrochemically active surface area (ECSA) values for Sa6, Sa7 and Sa8 (Figure S28) indicate similar populations of active sites, thus the adsorption and transfer of reactants to perform the NRR follows nearly common patterns in terms of speed. Possibly the capping ligands used during the synthesis of Sa6 deteriorated the electrocatalytic activity of the sharp tips and edges of its anisotropic structure by complicating the undisturbed access of reactants on these active sites [53]. Similar FE values have been obtained also for metal dichalcogenide materials with graphene-like structures such as c-MoS2 nanosheets grown on carbon cloth by hydrothermal method or MoSe2-based composites [50,54].…”
Section: Nitrogen Reduction Reactionmentioning
confidence: 53%
“…Overall, the relatively similar electrochemically active surface area (ECSA) values for Sa6, Sa7 and Sa8 (Figure S28) indicate similar populations of active sites, thus the adsorption and transfer of reactants to perform the NRR follows nearly common patterns in terms of speed. Possibly the capping ligands used during the synthesis of Sa6 deteriorated the electrocatalytic activity of the sharp tips and edges of its anisotropic structure by complicating the undisturbed access of reactants on these active sites [53]. Similar FE values have been obtained also for metal dichalcogenide materials with graphene-like structures such as c-MoS2 nanosheets grown on carbon cloth by hydrothermal method or MoSe2-based composites [50,54].…”
Section: Nitrogen Reduction Reactionmentioning
confidence: 53%
“…Still, such a negative effect depends also on the type of surfactant used. For instance, cationic surfactants are not suitable for catalysts with negative charges on their surfaces . We have previously shown that branched polyethyleneimine (PEI) allows noble metal nanostructures such as Pd and Au–Pt to exhibit remarkable catalytic and electrocatalytic performance, respectively. , Therefore, in sample Bi-S3, we kept the same conditions as in Bi-S2 with the exception of the use of PEI instead of PSS.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Transition-metal oxide nanocrystals are attractive for many different applications in energy conversion, storage, and photocatalysis due to their generally excellent chemical and thermal stability and their high surface area-to-volume ratio. To advance the fundamental understanding and ultimate application of these nanomaterials, it is essential to develop synthetic methods that provide access to high-quality samples with controlled size, crystal structure, composition, and morphology . Over the last two decades, heat-up and hot-injection methods involving the reaction of precursors at elevated temperature and ambient pressure in high-boiling organic solvents have evolved to provide exquisite control over noble metal and metal chalcogenide semiconductor nanocrystals. Ternary and alloyed materials with controlled compositions, core–shell structures, , and exceptionally high monodispersity in both isotropic and anisotropic morphologies are all accessible for these materials. In contrast, transition-metal oxide nanomaterials, particularly ternary metal oxide nanocrystals, often cannot be made using these well-developed colloidal techniques.…”
Section: Introductionmentioning
confidence: 99%